AUGMENTED BLOOD PRESSURE VARIABILITY FOLLOWING CONTINUOUS INFUSION OF NORADRENALINE IN RATS. (April 2021) - Jiang, Danfeng; Kawagoe, Yukiko; Asada, Yujiro; Kitamura, Kazuo; Kato, Johji
Abstract : Objective: Augmented blood pressure (BP) variability has been shown to be an independent cardiovascular risk factor. Activity of the sympathetic nervous system is an important determinant factor of the 24-h profile of BP variability, although it is unknown whether persistent adrenergic activation causes augmented BP variability or not. Here we report that continuous infusion of noradrenalin augments 24-h BP variability in rats, and our efforts were also made to explore the mechanism of action through which noradrenalin exerted this effect. Design and method: Nine-week-old male Wistar rats maintained under a 12-h light and 12-h dark cycle were continuously infused with subcutaneous 30 mg/h noradrenalin, 150 mg/h of the a1-adrenergic agonist phenylephrine, or 30 mg/h of the non-selective b-agonist isoproterenol, for 14 days. Noradrenalin-infused rats were also administered either oral 5 mg/day prazosin, an a1-blocker, or 50 mg/day atenolol, a b1-blocker, during the infusion period. BP variability was evaluated before and after 7 and 14 days of the infusion, using a coefficient of variation (CV) of BP recorded every 15 min under an unrestrained condition via an abdominal aortic catheter by a radiotelemetry system. Results: Continuous infusion of noradrenalin significantly increased BP variability at 7 and 14 days, slightly elevating BP levels, and this increase was observed similarly in the light and dark cycles. Noradrenalin-induced augmentation of BP variability was partially attenuated by oral administration of prazosin, but not by atenolol. This action of noradrenalin was mimicked by continuous infusion of phenylephrine, while isoproterenol failed to affect the BP variability. Conclusions: Continuous infusion of noradrenalin increased BP variability in rats through an a1-adrenergic receptor-mediated mechanism, suggesting that the noradrenalin-infused rat is an animal model of augmented BP variability induced by persistent adrenergic activation. This model could be useful in pharmacological screening of the suppressive action of candidate drugs on augmented BP variability in vivo.